Open field trials of food-grade gum in California and Oregon as a behavioral control for Drosophila suzukii Matsumura (Diptera: Drosophilidae) - Tait, Gabriella; Zhu, Tingyu; Klick, Jimmy; Ganjisaffar, Fatemeh; Castillo, Claira; Kennedy, Ryan; Thomas, Hillary; Adams, Christopher; Pfab, Ferdinand; Mermer, Serhan; Mirandola, Enrico; Xue, Lan; et al. (Frontiers in Insect Science, 2023)
The invasion of Drosophila suzukii, spotted-wing drosophila, across Europe and the US has led to economic losses for berry and cherry growers, and increased insecticide applications to protect fruit from damage. Commercial production relies heavily on unsustainable use of conventional toxic insecticides. Non-toxic insecticide strategies are necessary to alleviate the disadvantages and non-target impacts of toxic conventional insecticides and improve Integrated Pest Management (IPM). A novel food-grade gum deployed on dispenser pads (GUM dispensers) was evaluated to mitigate D. suzukii crop damage in five commercial crops and nine locations. Trials were conducted at a rate of 124 dispensers per hectare in cherry, wine grape, blueberry, raspberry, and blackberry in California and Oregon, USA during 2019 and 2020. The majority of trials with the food-grade gum resulted in a reduction of D. suzukii egg laying in susceptible fruit. In some cases such damage was reduced by up to 78%. Overall, results from our meta-analysis showed highly significant differences between GUM treatments and the untreated control. Modeling simulations suggest a synergistic reduction of D. suzukii damage when used in combination with Spinosad (Entrust SC) insecticide. These data illustrate commercial value of this tool as a sustainable alternative to manage D. suzukii populations within a systems approach.